Soviet Lithuanian New Year Greeting Card: Semiotics of Recto - Atminytė, Evelina (Semiotika, 2022)
The article discusses the semiotics of greeting card with focus on the discursive configuration of the recto side. The aim is twofold: to examine the possible ways image and verbal text are combined and identify the meaning produced by its different configurations. Soviet Lithuanian New Year greeting cards (dated from the late 1950s to 1989) are analyzed to accomplish the study. The methodological approach is compound. The guidelines of Greimasian theory of semiotics and Tartu-Moscow semiotic school as well as the ideas of Jacques Fontanille and Jean-Marie Floch are used to perform the study. The discourse analysis revealed that when placed on the recto side greeting text both anchors the content of the image and acts as a performative utterance. Depending on the specific configuration of the recto side and the material aspects of a greeting card, the role of enunciator can be subjected either to the artist or image figures. However, in some cases the performative function becomes secondary. For example, when playfulness established by the interrelation of image and verbal text is given priority over the greeting act.
Keywords: New Year greeting card; semiotics; recto; performativity; enunciative instance